Answer:
(2, - 4), (3, - 2)
Explanation:
Given the 2 equations
y - 2x = - 8 → (1)
x² - 3x - y = 2 → (2)
Rearrange (1) expressing y in terms of x
y = 2x - 8 → (3)
Substitute y = 2x - 8 in (2)
x² - 3x - 2x + 8 = 2
x² - 5x + 6 = 0 ← in standard form
(x - 2)(x - 3) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 2 = 0 ⇒ x = 2
x - 3 = 0 ⇒ x = 3
Substitute these values into (3) for corresponding values of y
x = 2 : y = (2 × 2) - 8 = 4 - 8 = - 4 ⇒ (2, - 4)
x = 3 : y = (2 × 3) - 8 = 6 - 8 = - 2 ⇒ (3, - 2)